Embodied Theories of Knowledge and the Evil Eye in the Roman World - Alvar Nuño, Antón (Journal of Cognitive Historiography, 2024)
This article aims at enriching current interpretations of the Evil Eye in the Roman world by applying embodied theories of knowledge to the social environments that triggered this belief. In general terms, religious belief is grounded on representational processes of the body and of its surrounding environment; these, together, organize specific mental reference-systems. In other words, actual experience is encoded in a mental frame that may later be used to make plausible explanations of a given situation. The psychosomatic feeling of envy (the Evil Eye was often conceptualized as an emotion) that the individual experienced at a given situation was processed into a complex socio-cultural reasoning that included 1) the identification and description of the pain suffered by the envious person (including the idea that the whole colour of their skin became bluish – livor); 2) the monitoring of one’s own moral conduct in the situation that triggered the feeling of envy; 3) the association of envy with a whole system of beliefs of mystical harm that could affect others; and 4) the possibility of restraining it. This experience fed the variety of cognitive strategies that individuals then elaborated in order to externalize their responsibility towards random misfortune.